Not as Cattle, Grazing in the Same Pasture. Friendship and Love in Aristotleand Hugh LaFollete - Krebs, Angelika (1999)
Should justice rule in close personal relationships, for example in the giving and taking between the sexes? Orare these relationships beyond justice? This paper defends the feminist call for justice (even) in close personal relationships against a common objection raised, among others, by Hugh LaFollette in 1996. According to this objection the call for justice undermines love; it tums close personal relationships into self-interested exchange relationships.